ANALISIS CERITA ROMANCE POPULER CINTA ABADI DAN PRIA, WANITA, DAN ANAK KARYA ERICH SEGAL - Heni Monika Deona (Universitas Nahdlatul Wathan Mataram, 2019)
Abstract Popular novel is a kind of novel that is very liked by many segments, children up to adults. These readers have each segmentation of their novel. There are many genres of novel, such as romance, mistery, thriller, detective, western, comedy, and adventure. Every genre has its reader. Romance novels is usually liked by women, western novel is liked by men, detective and adventure novel is liked by children, comedy novel is liked by teenagers. This writing will analyzed the romance of Erich Segal novels, they are Cinta Abadi, and Pria, Wanita dan Anak. Keywords: romance, women, populer